The Design and Contributions of Innovative Actions Aimed at Enhancing Women’s Visibility in Diverse Areas of Knowledge. An Integrated University Proposal - Guadamillas Gómez, María Victoria (Comunicación y Género [Communication and Gender], 2021)
This paper describes an innovation project which main aim is to generate a shared work stream to create teaching materials and resources in order to teach mother or foreign languages in diverse educational levels. These materials will be oriented to visualise women and their achievements in order to contribute to the empowerment of future and present generations as well as to fight for other global goals such as the gender gap in some areas or the equality between men and women in diverse fields of knowledge. Firstly, the project is contextualised and justified within the university and the foreign language area, in particular. Later, some lines of work and the possible guidelines of each of them are explored. Finally, our attention is paid to the evaluation strategies. The previous considerations allow us to respond and contribute to the global worries stated in the Agenda 2030 as well as in other scientific studies that have underlined the under-representation of women in several educational materials.